Analisis Spasial Temporal Indeks Kekeringan dan Sebaran Hotspot dengan Pemanfaatan Data Satelit pada Kabupaten Ogan Komering Ilir dengan Metode Keetch Byram Drought Index (KBDI): Spatial Temporal Analysis of Drought Index and Distribution of Hotspots Using Satellite Data in Ogan Komering Ilir District Using the Keetch Byram Drought Index (KBDI) Method - Gunawan, Taufik Ari; Imroatul Chalimah Juliana; Reini Silvia Ilmiaty; Rahmadhina Aji Pertiwi (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2022)
Frequent droughts cause forest and land fires during the long dry season. Therefore, it is necessary to overcome the problem of drought. However, currently, information about drought is still lacking even though it is very much needed. This is the background for researching the analysis of the drought index. This study will analyze spatially and temporally the drought that occurred in Ogan Komering Ilir Regency. Due to the limited data from the observation station, data from the Climate Forecast System Reanalysis (CFSR) was used and calculated using the Keetch Byram Drought Index (KBDI) method, then visualized using the Geographic Information System (GIS) application to map the distribution of drought index, hotspot distribution, and land cover. Based on this analysis, it can be seen that in Ogan Komering Ilir Regency, extreme drought often occurs in September in areas dominated by shrubs and dry forests. After being corrected, the distribution of the drought index, the distribution of hotspots, and land cover showed a strong correlation.